Excessive food price variability early warning system: Incorporating fertilizer prices - Yao, Feng; Hernandez, Manuel A. (International Food Policy Research Institute, 2025)
Low adoption of improved land management practices, including fertilizer use, is one of the main factors for low agricultural productivity in many developing countries. Rising agricultural productivity in many countries has been accompanied by greater fertilizer use. For example, sub-Saharan African countries, characterized by low agricultural productivity, have a very low fertilizer application rate, averaging 10 kilograms per hectare (kg/ha) of nutrients of arable land, compared to 288 kg/ha in a high-income country (Hernandez and Torero, 2011). Considering the essential role that agriculture plays in the rural economy of many developing countries, many policies have been implemented to encourage sustainable fertilizer adoption. The effectiveness of different mechanisms remains though a topic of discussion. Hernandez and Torero (2013) and Hernandez and Torero (2018), for instance, note that fertilizer prices are generally higher in more concentrated markets at the global and local level. The authors argue that better understanding the dynamics of fertilizer prices in international markets can help in designing policies that promote sustainable fertilizer use in developing countries, which are increasingly dependent on imported fertilizer.